Automating what? Scholastic products and instructional automation in virtual schooling. - Nespor, Jan; Fitz, Julie (Discourse: Studies in the Cultural Politics of Education, 2023)
Schools produce multiple products and digitization articulates with them in different ways. In this paper we expand the frame for analyzing instructional automation by examining its implications for three scholastic products – embodied learning, grades and test scores, and the narratives that connect the two. We draw on data from interviews with 47 teachers in four full-time virtual elementary and secondary schools in the US to argue that at present most of the actual work of automation in virtual schools is focused on the production of marks and grades, and that the narrative products of digitization efforts – routinization discourses, potentials discourse, and 'live' teaching discourse, play key roles in shaping how we understand the connections between those products and student learning.